2021
DOI: 10.1021/acs.orglett.0c04192
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Dual Coupling Reaction of 2-Iodobiphenyls with o-Bromoanilines through C–H Activation: An Approach for the Synthesis of Tribenzo[b,d,f]azepines

Abstract: A novel and straightforward approach for the synthesis of tribenzo­[b,d,f]­azepines starting from 2-iodobiphenyls and 2-bromoanilines has been developed. A wide range of tribenzo­[b,d,f]­azepines were obtained in good to excellent yields via a cascade intermolecular palladium-catalyzed C–H activation/dual coupling reaction. C,C-palladacycles, which are generated by C–H activation of 2-iodobiphenyls, should be the reaction intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 59 publications
1
16
1
Order By: Relevance
“…For the scope of the biphenyl 86, multiply substituted biphenyls were tested and the result showed that strong electron-donating groups like OMe on the para position of both rings increase the efficacy. [85]…”
Section: Seven-membered Ring Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the scope of the biphenyl 86, multiply substituted biphenyls were tested and the result showed that strong electron-donating groups like OMe on the para position of both rings increase the efficacy. [85]…”
Section: Seven-membered Ring Formationmentioning
confidence: 99%
“…The presence of Me on the amine group of aniline in 87 did not affect the reaction negatively, but the presence of Ph group in the same position reduced the yield dramatically. For the scope of the biphenyl 86 , multiply substituted biphenyls were tested and the result showed that strong electron‐donating groups like OMe on the para position of both rings increase the efficacy [85] …”
Section: Recent Ullman‐goldberg And/or Buchwald‐hartwig Reports In Li...mentioning
confidence: 99%
“…On the basis of the experimental results and previous reports, a possible reaction mechanism was proposed in Scheme . Initially, the oxidative addition of 2-iodobiphenyls 1 to Pd(0) generates Pd­(II) intermediates A .…”
Section: Resultsmentioning
confidence: 99%
“…A variety of substituted tribenzo­[ b , d , f ]­azepines can be synthesized according to this method (Scheme C). During the preparation of this manuscript, a similar work was reported by Zhang’s group …”
Section: Introductionmentioning
confidence: 81%
“…Recently, a Pd-catalysed dual coupling of 2-iodobiphenyls and 2-bromoanilianes furnishing tribenzo [b,d,f]azepines was reported by Zhang and colleagues. 79 In the presence of 5 mol% Pd(OAc) 2 , phosphine ligand and Cs 2 CO 3 , 24 azepines, they were synthesized in good to excellent yields. This transformation featured the sequential C-C and C-N bond forming through the C-H activation process (Scheme 50).…”
Section: Ring Formation Via [4 + 3] Type Of Cyclizationmentioning
confidence: 99%